PENERAPAN MODEL PROBEX DAPAT MENINGKATKAN HASIL BELAJAR IPA SISWA KELAS IV SD NEGERI 011 DESA BARU KECAMATAN SIAK HULU KABUPATEN KAMPAR - Lismarni (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2018)
This research is motivated by the low level of learning outcomes of science in fourth-grade students of SD Negeri 011 Desa Baru. For this reason, improvements to the learning process were carried out by applying the PROBEX learning model. This research is a classroom action research conducted in class IV SD Negeri 011 Baru Village with a total of 28 students. The data used in this study are students' learning outcomes. Based on the results of the study obtained data that learning outcomes have increased after applying the PROBEX model. This can be seen from the average completeness of student learning outcomes in completeness pre- cycle only 36% after the first cycle reached 64.28% and after the implementation of the second cycle reached 78.5%. Based on this acquisition, it can be concluded that the PROBEX model can improve the science learning outcomes of fourth-grade students of SD Negeri 011 Desa Baru.